ANALISIS IMPLEMENTASI KEBIJAKAN PEMUNGUTAN RETRIBUSI RUMAH POTONG HEWAN DI KABUPATEN PARIGI MOUTONG - Hildawaty, Jumaria (Katalogis, 2014)
The  objectives  of  the  research  were  to  find  out  and  describe   Analysis  of  PolicyImplementation on Butcher House Retribution Collectting in Parigi Moutong Regency .The researcher employed theory of Edward III coverring factors such as Communication, Resources, Disposition and Bureaucratic Structure. This research employed qualitative descriptive methodology. Based on the observation results in the field, the researcher concluded that butcher house in Parigi Moutong Regency have not run well and not totally effective. It was seen from four aspects  observed,  the aspect  of  communication,  resources  and  disposition  have not  supported because they have not become priority program in supporting Rrgional Real Income.